PENGARUH PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA MATERI MENGENAL TUBUH TUMBUHAN KELAS IV SDN TANAMERA I - Abdi, Zainal; Jamilah; Tri Sukitman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the application of the contextual learning model on student learning outcomes on the material on knowing plant bodies in grade IV of SDN Tanamera 1. This study uses the Pre-Experimental Design method with the type of One Group Pretest-Posttest Design, where students are given a pretest before learning and a posttest after the application of the contextual learning model. Data were analyzed using the Shapiro-Wilk normality test, Paired Samples Correlations, and Paired Samples T-Test. The results of the normality test showed that the pretest and posttest data were distributed normally (p > 0.05).Statistical analysis shows that there is an increase in the average score from 47.86 (pretest) to 59.29 (posttest). However, the correlation between pretest and posttest was low (r = -0.171, p = 0.558), which indicates that the improvement in posttest scores is not entirely dependent on pretest scores. The results of the Paired Samples T-Test showed a significant difference between the pretest and the posttest (t = -44.035, p = 0.000). Based on the results of the study, it can be concluded that the application of the contextual learning model has a significant influence on improving student learning outcomes. Therefore, this model is recommended to be applied in learning to improve understanding of concepts in a more meaningful way